The dimensionality of emotional intelligence: Evidence for a four-factor model for post-Soviet and Central Asian adolescents - Taibolatov, Kuandyk; Courtney, Matthew; Zhapparova, Aikorkem; Hernández-Torrano, Daniel (Anales de Psicología / Annals of Psychology, 2024)
Introduction: The study of emotional intelligence (EI) has garnered significant attention due to its relevance to diverse age- and population-groups, and persons of various social and academic backgrounds. The capacity for an individual to effectively understand and manage one’s own emotions and understand and manage the emotions of others has been identified as important life skill and antecedent to personal, social, and professional success. While the dimensionality of EI has been explored extensively in Western contexts, there is a relative dearth of research in post-Soviet and Central Asian contexts. Methodology: Building upon the EI instrumentation developed in Russia by Lyusin and a large sample of adolescents (N = 658) from 12 schools, we find very little differences in average levels of EI in the schools sampled. Thereafter, using first-order confirmatory factor analysis, this study finds evidence for a Four-Factor Model of EI inclusive of Understanding and Managing One’s Own Emotions, and Understanding and Managing Others’ Emotions. Results: The model exhibits adequate model fit, discriminant validity, inter-factor correlations similar to those in other studies, and is strongly invariant for gender (though partially invariant for language). We also find evidence for female adolescents exhibiting slightly higher levels of Understanding Other’s Emotions, and lower levels of Managing Own Emotions. Conclusions: The four-factor model may be a useful tool for gauging the EI of adolescents, though further research as to its utility in other post-Soviet, Central Asian, and other contexts is required.